The effects of weight class athletes’ nutrient consumptions and eating habits on their depression-anxiety-stress levels - Yüceloğlu Keskin, Deniz Özge; Kabadayı, Menderes; Bostancı, Özgür; Bayram, Levent; Derebaşı, Deniz Günay (Progress in Nutrition, 2020)
Diet is important in sports in terms of having an influence on bodily and mental health besides sportive performance. The objective of this study is to find out the effects of dietary habits and eating attitudes on moods of weight class athletes. The study was conducted with a total of 60 athletes -33 wrestlers who participated in Turkey Men’s Greco-Roman Wrestling National Team Preparation Camp, 18 wrestlers who participated in Turkey Men’s Freestyle National Team Preparation Camp and 9 judokas who participated in Turkey Men’s Judo National Team Preparation Camp during the years 2013 and 2014. Athletes’ demographic characteristics and information about their three-day eating habits were found, eating attitudes test (EAT) and Depression, Anxiety and Stress Scales (DASS-42) were applied and some of their anthropometric measurements were found. Student-t, Mann Whitney U, Anova and Kruskal tests were used for the statistical analysis of data. Statistically significant difference was found between the EAT scores of Greco-roman wrestlers and freestyle wrestlers and EAT scores of Greco-roman wrestlers were found to be higher (p<0,05). Average carbohydrate intake and stress scores of athletes whose stress scores were higher than normal were found to be significantly higher when compared with the group with normal stress scores (p<0,05). Unhealthy diets which athletes follow to keep body weight under control both damage the athletes’ diet and negatively affect their moods.